Effects of chlortetracycline and copper supplementation on levels of antimicrobial resistance in the feces of weaned pigs - Agga, Getahun Ejeta (Kansas State University, 2013)
The use of antibiotics in food animals is of major concern as a purported cause of antimicrobial resistance (AMR) in human pathogens; as a result, alternatives to in-feed antibiotics such as heavy metals have been proposed. The effect of copper and CTC supplementation in weaned pigs on AMR in the gut microbiota was evaluated. Four treatment groups: control, copper, chlortetracycline (CTC), and copper plus CTC were randomly allocated to 32 pens with five pigs per pen. Fecal samples (n = 576) were collected weekly from three pigs per pen over six weeks and two Escherichia coli isolates per sample were tested phenotypically for antimicrobial and copper susceptibilities and genotypically for the presence of tetracycline (tet), copper (pcoD) and ceftiofur bla[subscript]C[subscript]M[subscript]Y₋₂) resistance genes. CTC-supplementation significantly increased tetracycline resistance and susceptibility to copper when compared with the control group. Copper supplementation decreased resistance to most of the antibiotics, including cephalosporins, over all treatment periods. However, copper supplementation did not affect minimum inhibitory concentrations of copper or detection of pcoD. While tetA and bla[subscript]C[subscript]M[subscript]Y₋₂ genes were associated with a higher multi-drug resistance (MDR), tetB and pcoD were associated with lower MDR. Supplementations of CTC or copper alone were associated with increased tetB prevalence; however, their combination was paradoxically associated with reduced prevalence. These studies indicate that E. coli isolates from the weaned pigs studied exhibit high levels of antibiotic resistance with diverse multi-resistant phenotypic profiles. In a related study, total fecal community DNA (n = 569) was used to detect 14 tet genes and to quantify gene copies of tetA, tetB, pcoD and bla[subscript]C[subscript]M[subscript]Y₋₂. CTC and copper plus CTC supplementation increased both the prevalence and gene copies of tetA, while decreasing both the prevalence and gene copies of tetB, when compared with the control group. The diversity of tet genes were reduced over time in the gut bacterial community. The roles of copper supplementation in pig production and pco-mediated copper resistance in E. coli need to be further explored since a strong negative association of pcoD, with both tetA and bla[subscript]C[subscript]M[subscript]Y₋₂, suggests there exist opportunities to select for a more innocuous resistance profile.
Keywords: Chlortetracycline and copper supplmentation; Pigs; Antimicrobial and copper resistance; E. coli; Ceftiofur; Tetracycline; Epidemiology (0766); Microbiology (0410); Veterinary Medicine (0778)